Odpowiedzi

2009-10-22T20:12:58+02:00
1. s= 12 km
t= 2h 10 min = 2 i 1/6 h
v= s/t = 12 km : 13/6 h = 12km * 6/13 h = 72km/13h = ok 5,5 km/h

2. s=18 km
t= 3 h 35 min = 3 i 7/12 h
v= s/t = 18km : 43/12 h = 18 km * 12/43 h = 216km/43h = ok 5 km/ h

5 4 5
Najlepsza Odpowiedź!
2009-10-22T20:14:50+02:00
S₁=12km
t₁=2 1/6h = 13/6h
s₂=18km
t₂=3 7/12h = 43/12h (3 35/60h = 7/12h

wzór na prędkość:
v=s/t
v₁=s₁/t₁ = 12km/ 13/6h = 12km* 6/13h ≈ 5,5km/h

v₂=s₂/t₂ = 18km/ 43/12h = 18km * 12/43h ≈ 5km/h
v₁>v₂

odp. Z większą średnią prędkością szedł pierwszy podróżnik



2 3 2